Apiarian Bioactives in Dentistry: A Narrative Review on Pulp Preservation and Regeneration - Turbatmath, Ketaki; Antony S, Delphine Priscilla (Journal of Neonatal Surgery, 2025)
Vital pulp therapy (VPT) seeks to preserve the structural and functional integrity of the dental pulp following caries or trauma. While synthetic biomaterials such as calcium hydroxide, mineral trioxide aggregate (MTA), and newer calcium silicate cements have improved outcomes, limitations in terms of solubility, cost, handling, and long-term success have stimulated the search for natural alternatives. Among these, apiarian-derived bioactives, particularly propolis and royal jelly have emerged as promising candidates due to their unique combination of antimicrobial, anti-inflammatory, antioxidant, and regenerative properties. Propolis, rich in flavonoids and phenolic acids, has demonstrated broad-spectrum antimicrobial action, modulation of inflammatory cytokines, and the ability to induce organized dentin bridge formation in pulp capping models [1,2]. Royal jelly, characterized by major royal jelly proteins and 10-hydroxy-2-decenoic acid (10-HDA), promotes fibroblast proliferation, collagen synthesis, and reparative dentinogenesis [3]. Evidence from in vitro, animal, and comparative studies suggests that their biological activity rivals or exceeds that of conventional materials in certain contexts. This narrative review consolidates current evidence on the role of apiarian bioactives in conservative dentistry and endodontics, with emphasis on pulp preservation and regeneration. Their potential for indigenous development, affordability, and sustainability further enhance their translational value. Future perspectives include nano-enhanced formulations, hybrid biomaterials, and rigorous clinical trials to validate their integration into mainstream vital pulp therapy.